2021
DOI: 10.2196/25358
|View full text |Cite
|
Sign up to set email alerts
|

Participant Perceptions of Facilitators and Barriers to Adherence in a Digital Mental Health Intervention for a Nonclinical Cohort: Content Analysis

Abstract: Background Digital mental health promotion interventions (MHPIs) present a scalable opportunity to attenuate the risk of mental health distress among nonclinical cohorts. However, adherence is frequently suboptimal, and little is known about participants’ perspectives concerning facilitators and barriers to adherence in community-based settings. Objective This study aimed to examine participants’ perceptions of facilitators and barriers to adherence in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
1
13
0
4
Order By: Relevance
“…It is noteworthy that this module is the most interactive of the program, in addition to providing a final graph as a product of such interaction. This characteristic is relevant as, in other studies, the interactivity factor was considered especially important for greater adherence to online interventions in health (7)(8) , and the graphic resources are associated with a lower cognitive effort for learning with the tool (9) .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It is noteworthy that this module is the most interactive of the program, in addition to providing a final graph as a product of such interaction. This characteristic is relevant as, in other studies, the interactivity factor was considered especially important for greater adherence to online interventions in health (7)(8) , and the graphic resources are associated with a lower cognitive effort for learning with the tool (9) .…”
Section: Discussionmentioning
confidence: 86%
“…The literature points out that studies on online strategies for mental health promotion should focus on interventions in which the most unique aspects of the participants are considered, such as personal characteristics and needs, to maintain the adherence of the target audience and maximize the possibility of approach effectiveness (2,8,11,(15)(16) . In this sense, the present study was developed with a very specific group, nursing students in the initial years of graduation, and used software developed especially for this population, considering their particularities and needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modulating factor might be the time availability. In a previous qualitative study [ 75 ], we reported that “time” was perceived as a major barrier to adherence for many participants, although the older participants expressed that retirement provided them with more time to adhere to the intervention. Notably, outcomes of a digital mental health intervention were shown to be related to higher levels of adherence such as higher levels of time spent on the digital platform, number of sessions completed, percentage of the program viewed, and number of activities compared to the control group [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…To gain further insight into participant perspectives, we conducted a qualitative study (Renfrew et al, 2021 ) using inductive thematic analysis to examine user perceptions regarding facilitators of, and barriers to, adherence. The provision of human support did not feature as a perceived facilitator of adherence.…”
Section: Human Supportmentioning
confidence: 99%